2018
DOI: 10.1086/696863
|View full text |Cite
|
Sign up to set email alerts
|

The Pathology of Hard Propaganda

Abstract: Authoritarian governments often impose crude and heavy-handed propaganda messages on society. Is such hard propaganda effective in sustaining authoritarian rule? With an original survey experiment featuring messages from China's ongoing propaganda campaign, this study finds that hard propaganda can backfire and worsen citizens' opinions of the regime, while at the same time signaling the state's power and reducing citizens' willingness to protest. Thus, hard propaganda can deter dissent and help maintain regim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
68
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 123 publications
(90 citation statements)
references
References 26 publications
(27 reference statements)
8
68
2
Order By: Relevance
“…On the other hand, the findings also reveal the uniqueness of the informal education impact when compared to regular propaganda channels, especially formal education. As shown in the empirical tests, the obedience-enforcement effect apparent in formal education does not explain the impact of PEDBs (Huang, 2015). These findings request scholars to rethink about the role of propaganda in authoritarian governance.…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations
“…On the other hand, the findings also reveal the uniqueness of the informal education impact when compared to regular propaganda channels, especially formal education. As shown in the empirical tests, the obedience-enforcement effect apparent in formal education does not explain the impact of PEDBs (Huang, 2015). These findings request scholars to rethink about the role of propaganda in authoritarian governance.…”
Section: Discussionmentioning
confidence: 73%
“…Nonetheless, these findings are consistent with findings in media propaganda. For instance, Chen and Shi () found that more frequent exposure to media propaganda (in the temporal dimension) reduces people's political trust in the government (see also Huang, ). This study manifests that the same mechanism also exists in the spatial dimension and can affect more than political trust but also support for the regime and obedience to the government.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, scholars could apply a similar experimental design when studying misperceptions concerning climate change (Nisbet, Cooper, and Garrett 2015), police violence and the criminal justice system (Esberg, Mummolo, and Westwood n.d.), immigration (Hopkins, Sides, and Citrin 2019), or issues related to health-care response (Deslatte 2020;Lewandowsky et al 2012). Outside of the U.S. context, scholars who focus on issues related to "fact checking" or propaganda (Graves and Cherubini 2016;Huang 2018) may also benefit from considering the role of ISI in modifying the effects of misperceptions. Regardless of the issue domain or context, our research encourages scholars to further consider the social context within which misinformation and corrections are embedded.…”
Section: Discussionmentioning
confidence: 99%